2014
DOI: 10.1007/s11136-014-0743-3
|View full text |Cite
|
Sign up to set email alerts
|

Measurement properties of questionnaires assessing participation in children and adolescents with a disability: a systematic review

Abstract: Studies of high methodological quality, using modern statistical methods, are needed to accurately assess the measurement properties of currently available questionnaires. Moreover, consensus is required on the definition of the construct 'participation' to determine content validity and to enable meaningful interpretation of outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 52 publications
0
47
0
4
Order By: Relevance
“…Frequently, information on measurement properties of instruments is combined across multiple populations (e.g. children with various and diverse conditions and disabilities) without analysing subgroups of different diagnostic groups . This can provide a broad overview of available and examined measures.…”
Section: Discussionmentioning
confidence: 99%
“…Frequently, information on measurement properties of instruments is combined across multiple populations (e.g. children with various and diverse conditions and disabilities) without analysing subgroups of different diagnostic groups . This can provide a broad overview of available and examined measures.…”
Section: Discussionmentioning
confidence: 99%
“…Enhancement of participation is often reported as the ultimate health and educational outcome and the primary goal of rehabilitation . Previous systematic literature reviews have examined the properties of available participation measurement tools, reported participation restrictions for people with disabilities, and identified supports and barriers to participation in people with disabilities . However, literature describing evidence‐based approaches to improving participation in people with disabilities is limited.…”
mentioning
confidence: 99%
“…The CASP measures children's extent of participation and restrictions in home, school and community life situations and activities compared with same‐age peers as reported by a parent or caregiver . The CASP was selected because, at the time of this study, it was evaluated most extensively, generally showing moderate positive results . It has been used in children from 3 years of age, and the Dutch version showed to have good measurement properties among a population of children with acquired brain injury …”
Section: Methodsmentioning
confidence: 99%
“…This instrument is not specifically targeted at children with VI, but is aimed at the evaluation of eye‐related concerns. As such, no instrument is currently available to measure developmentally‐appropriate participation specifically for children with VI …”
Section: Introductionmentioning
confidence: 99%